ETOS KERJA DAN INSENTIF GURU PERSPEKTIF ISLAM: Telaah di MTs. Miftahul Ulum Purwakarta - Supiana, Supiana; Zaqiah, Qiqi Yulianti; Adam, Deden Kurnia; Nahar, Agus Samsul; Komala, Euis (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study explores the evolution of the mudarabah contract from a historical perspective to its prospects for application in the modern banking system. Using a literature review method, with a research focus on the evolution of the mudarabah contract over time and its prospects for application in the modern banking system. Historical analysis shows how mudarabah has adapted to the changing socioeconomic and financial regulatory challenges over time, as well as the evolution of its practice based on the principle of profit sharing and Islamic commercial ethics. The results of the study show that innovation and adaptation in Islamic financial products, including mudarabah contracts, have strengthened their relevance in the modern era, indicating significant growth in global Islamic banking. This article closes by discussing the prospects of mudarabah contracts as ethical and sustainable financial instruments in the modern banking ecosystem, given the increasing demand for responsible and fair financial alternatives, as well as the important role of financial technology in expanding the reach and efficiency of sharia financial transactions.